Wafer‐Scale Van der Waals Assembly of Free‐Standing Near Atom Thickness Hetero‐Membranes for Flexible Photo‐Detectors. (21st June 2021) - Shawkat, Mashiyat Sumaiya; Han, Sang Sub; Chung, Hee‐Suk; Mofid, Sohrab Alex; Yoo, Changhyeon; Jung, Yeonwoong
Abstract: Heterogeneous integrations of functionally and chemically distinct materials have been explored to develop promising building blocks for opto‐electronic device applications. Recently, the Van der Waals (vdW)‐assembly of near atom thickness materials has provided excellent opportunities beyond what has been previously been difficult to realize. However, its up‐to‐date demonstrations remain far from achieving the scalability and versatility demanded for practical device applications, that is, the integration is generally demonstrated with intrinsically layered 2D materials of very small lateral dimensions. Herein, the large centimeter‐scale vdW assembly of two different materials with structurally, chemically, and functionally distinct properties, that is, 2D platinum ditelluride (PtTe2 ) metallic multilayers and non‐layered 3D semiconducting platinum sulfide (PtS) are reported. Both materials are precisely delaminated from their growth wafers inside water and are subsequently integrated on unconventional substrates of desired functionalities. The large‐area vdW‐assembled 2D/3D PtTe2 /PtS hetero‐materials on flexible substrates exhibit an excellent photodetection in a spectral range of visible‐to‐near infrared (NIR) wavelength, which is well preserved under severe mechanical deformation. This study paves the way for exploring large‐area flexible opto‐electronic devices solely based on near atom thickness materials. Abstract : Wafer‐scale Van der Waals heterogeneous integrations of semiconducting 3D PtS thin films and metallic 2D PtTe2 layers onto mechanically flexible substrates are demonstrated by their controlled water‐assisted delamination. The resulting large‐area 2D/3D heterojunctions exhibit excellent visible‐to‐near infrared photo‐responsivenenss which is well preserved even under severe mechanical deformation.